2015
DOI: 10.14740/jocmr2182w
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial Tuberculosis Without Lung Involvement

Abstract: Endotracheal tuberculosis (ETTB) is an infrequent form of tuberculosis whose major feature is the infection of the tracheobronchial tree by Mycobacterium tuberculosis. This case presents a 73-year-old man admitted to our hospital with fatigue, weakness, dry cough and weight loss. His chest X-ray was normal but the high resolution computed tomography (HRCT) showed normal parenchyma images with mediastinal and hilar lymphadenopathy. There was inflammation of the tracheal wall and infiltrates in pavement epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“… 5 The majority of TBTB cases are secondary to PTB, and some patients with TBTB may not necessarily have lung parenchyma involvement. 6 According to reports, TBTB is observed in 10% to 39% of patients with PTB. 7 , 8 TBTB can result in thickening of the tube wall, narrowing of the tube lumen, bronchial dissemination, bronchiectasis, and may also contribute to airway stenosis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The majority of TBTB cases are secondary to PTB, and some patients with TBTB may not necessarily have lung parenchyma involvement. 6 According to reports, TBTB is observed in 10% to 39% of patients with PTB. 7 , 8 TBTB can result in thickening of the tube wall, narrowing of the tube lumen, bronchial dissemination, bronchiectasis, and may also contribute to airway stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…TBTB is a specific subtype of PTB in which the tuberculous lesions are primarily located in the wall of airway, and are not necessarily accompanied by involvement of pulmonary parenchyma[ 9 , 11 ]. Pathological changes in the airway wall can lead to airway stenosis in up to 90% of TBTB patients, especially in the late stage of disease; this is a major cause of mortality in these patients[ 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 10-20% of cases present with normal chest radiographs [14]. Campos et al [15] reported a patient with a normal chest X-ray whose bronchoscopy showed granular TBTB. The diagnosis of TBTB remains a challenge for clinicians since initially it shows non-specific signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%